Luke the Physician and other studies in the history of religion - Ramsay, William Mitchell, Sir, 1851-1939 (London, UK Hodder and Stoughton, 1908)
Includes bibliographical references and index.
Donated by the late Thomas Denton.
Keywords: Luke, the apostle, Saint -- Biographies